Strategi Digital Marketing pada Berlian Florist di Kota Cilegon - Melly Maya Masyitoh (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2025)
This research aims to find out the digital marketing research strategy carried out by Berlian Florist to increase consumer interest and to find out about what social media is used by Berlian Florist. The research method used is descriptive qualitative, using observation, interview and documentation techniques. The research subjects were Berlian Florist owners and employees. The object of this research is the marketing strategy through digital marketing at Berlian Florist. The research results show that 1) Digital marketing by Berlian Florist is marketing via social media Instagram and WhatsApp. 2) The advantage of the digital marketing strategy implemented is that social media is the main alternative for marketing businesses in the current era, implementing regular content creation, and also getting prices. which is cheaper than other flower shops 3) Obstacles and solutions that can be taken are an unstable internet network, less efficient time management by notifying customers in advance to order in advance so they can choose various kinds of flowers, and facing competitors who have the same business solution as provide discounts to customers.